The World's fastest motorcycles - Martin, John. (Mankato, Minn. : Capstone Press, 1994)
This book tells about some of the fastest motorcycles with color photographs and easy to read text.
Includes index.
Includes glossary.
Includes bibliography.
920
Accelerated Reader AR
Keywords: Motorcycles; Motorcycle racing